SafeTrack: Secure Tracking Protocol for Mobile Sensor Nodes in Unstable Wireless Sensor Networks - Ali Adnan Al-Khazraji; Fatimah Abdulridha Rashid (IEEE Access)
In this paper, we present SafeTrack, a novel, secure tracking protocol specifically for mobile sensor nodes in unstable wireless sensor networks (UWSNs). To the best of our knowledge, the proposed framework addresses the main challenges, including dynamic network topology, energy constraints, and Sybil and impersonation attacks. In SafeTrack, we introduce a Dual Layer Security Framework (DLSF), which a lightweight cryptographic technique is paired with a trust based approach to provide robust node authentication and secured communication. It also incorporates an Adaptive Routing Algorithm (ARA) and an Energy Optimization Module (EOM) to enable both efficient resource utilization and resilience to changes in dynamic network conditions. Simulation and performance analysis show that SafeTrack performs much better than any previous state of the art protocol. This results in a 64% improvement in localization accuracy, 24.1% higher energy retention, and 51.1% lower latency, while achieving optimal performance even in highly unstable environments. We validate scalability of the framework with support for up to 300 nodes, which is far beyond what other protocols can do. Additionally, SafeTrack demonstrates a 70.6% improvement in network throughput, providing the ability to support high loads of traffic. SafeTrack is novel in that it combines advanced security and adaptive optimization techniques specifically designed for UWSNs. Using this innovative approach not only improves network reliability and security but also provides sustainability in energy constrained environments. The results demonstrate the feasibility and effectiveness of SafeTrack, positioning it in the vanguard of solutions for real world applications in smart cities, healthcare systems and industrial IoT.